Cybercrime and cybersecurity in India: causes, consequences and implications for the future - Kshetri, Nir (Crime, law and social change, 2016)
Cybercrime is rising rapidly in India. Developing economies such as India face unique cybercrime risks. This paper examines cybercrime and cybersecurity in India. The literature on which this paper draws is diverse, encompassing the work of economists, criminologists, institutionalists and international relations theorists. We develop a framework that delineates the relationships of formal and informal institutions, various causes of prosperity and poverty and international relations related aspects with cybercrime and cybersecurity and apply it to analyze the cybercrime and cybersecurity situations in India. The findings suggest that developmental, institutional and international relations issues are significant to cybercrime and cybersecurity in developing countries.